Deepening and transferring twenty-first century learning through a lower secondary Integrated Science module. (3rd July 2017) - Thang, Fong Kwan; Koh, Joyce Hwee Ling
ABSTRACT: A secondary school in Singapore incorporated twenty-first century learning into their science curriculum through an inquiry-based Integrated Science module. This study examines Secondary 2 students' perceptions of twenty-first century learning through this module. Through pre- and post-study surveys of 227 students and focus group interviews with nine students, it was found that the Integrated Science module deepened students' confidence with self-directed learning and authentic problem-solving whereas students' confidence with critical thinking positively predicted students' end-of-year results. Through this module, students acquired skills related to time management, information analysis, the use of information communications technologies and presentation that they transferred to the learning of their other academic subjects. The implications for designing twenty-first century learning experiences in schools are discussed.